A model curriculum for aspect-oriented software development - CLARKE, SIOBHAN (IEEE, 2006)
As new software engineering techniques emerge, there's a cognitive shift in how developers approach a problem's analysis and how they design and implement its software-based solution. Future software engineers must be appropriately and effectively trained in new techniques' fundamentals and applications. With techniques becoming more mature, such training moves beyond specialized industrial courses into postgraduate curricula (as advanced topics) and subsequently into undergraduate curricula. A model curriculum for aspect-oriented software development provides guidelines about fundamentals, a common framework, and a step toward developing a body of knowledge
PUBLISHED
Keywords: aspect-oriented programming; AOP